Hubungan Faktor Pekerjaan dengan Stres Kerja pada Perawat di Rumah Sakit Daerah Jakarta Timur - Muzakir, Haris; Islam, Azizah Fajar (Poltekkes Kemenkes Maluku, 2023)
Nurses have an essential task and important role in hospital services. The increase in hospital services will affect the performance of nurses. Nurses are required to do quality work and provide professional services to patients. Nurses have more medical actions than other medical workers. This condition gives nurses more significant work pressure and increases stress levels. This study aims to determine the relationship between work factors and work stress experienced by nurses. The type of research is a quantitative research using a cross-sectional approach. The population in this study were nurses who worked in Pondok Kopi Islamic Hospital, East Jakarta. The total population in this research is 191, and the samples taken were 125 people. This study used a cross-sectional approach. The results showed that 53 nurses (42.4%) experienced work stress, and 72 (57.6%) did not experience work stress. The bivariate analysis results show a significant association between job demands, social support, interpersonal relationships, roles and organisational changes with job stress. There is also an insignificant association between control over work and job stress.